ANALYSIS OF RELIGIOUS TEACHING AND SOCIOCULTURAL ENVIRONMENT IN RURAL SCHOOLS - Šarkaitė, Jolita (Acta Paedagogica Vilnensia, 2008)
The articl analyse Catholic religious program, which was certified in 2006 and Lithuania’s sociocultural environment in rural areas. Sociocultural environment is an important factor that forms schoolchildren’s intellectual development. So, responding to environmental challenges, religious teaching can benefit schoolchildren’s spiritual perfection in secularized world and in a particular environment. Religious teaching in common rural area is the only way to develop Christian values but it has not been researched in sociocultural context yet. With reference to quantitative survey, teachers were interviewed to find out their attitude to religious lessons in sociocultural context of rural areas. The teachers of religious working in rural basic schools have not been realized the demand regarding sociocultural environment of rural areas in religious teaching; moreover, it does not respond in practice.
Keywords: socio-cultural environment in the village; primary schools; teaching religion; religion teacher